PENGARUH PENILAIAN PRESTASI KERJA TERHADAP KINERKA KARYAWAN DENGAN PROMOSI JABATAN SEBAGAI VARIABEL INTERVENING PADA ALPHA HOTEL PEKANBARU - Siska Nindriani; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research is motivated by the importance of human resource management in moving the company. In a company managing human resources properly is one way to increase employee performance. In achieving good performance, employees who have high work power are needed to anticipate the opportunities and challenges of an increasingly competitive business environment. This research was conducted at Alpha Hotel Pekanbaru, Jalan Imam Munandar No. 17, Tangkerang Utara, Kec. Bukit Raya Pekkanbaru. The purpose of this study was to determine the level of employee performance at Alpha Hotel Pekanbaru. The research sample was taken as many as 76 respondents but due to the impact of Covid19, the researcher only obtained 36 respondents using the census method. In this research, the methods used are descriptive and quantitative. The data obtained from the results of interviews and distributing questionnaires / questionnaires were then tested by SEM and PLS analysis. . Data analysis using linear regression analysis with the help of SmartPLS 3.0 software. From the results of the tests carried out, it shows that job performance appraisal has a positive but insignificant effect on employee performance, job performance appraisals have a positive and significant effect on job promotion, job promotion has a positive and significant effect on employee performance, and job performance assessment through job promotion has a simultaneous effect on employee performance.  Keywords: Job Performance Assessment, Job Promotion, Employee Performance